Mejora en la gestión del almacén de la empresa Becatel Perú S.A.C. para la disminución de costos por demoras en campo - Campos Vasquez, Henry (2019)
The present research work focuses on the improvement of warehouse management of the company Becatel Peru S.A.C. with the objective of reducing operating costs due to delays in the field. The samples considered for this analysis are the costs for delays in the field due to lack of material or tools in the projects executed by Becatel Perú S.A.C. In the period of August 2017-February 2018. The techniques used for data collection have been direct observation, analysis of records, discussions; For the analysis of the data, techniques such as the Pareto diagram, dispersion diagrams, flow diagrams were used, resulting as main problems, that there is no structure or order in the activities carried out, obsolete control methods, lack of records and controls. for the implementation of the improvements has been necessary to carry out various activities: initial inventory, ordering and labeling, implementation of a module developed in an Excel spreadsheet for the control of entries and exits, documentation of the activities that make up the various processes ordered in the warehouse area. We identified three main causes that represent the 50% that originates the delays: shortage of materials, lack of stock quantity and the difficult location of the materials. The operating costs for initial field delays have averaged 20% of the value of the project, which after the improvement in warehouse management has managed to decrease and represent between 1% and 2% of the value of the project